SALT LOADING INFLUENCE ON SULEMA NEPHROPATHY BACKGROUND OVER GLUTATIONPEROXYDASA ACTIVITY IN THE RATS KIDNEYS - Velika, A.Ya.; Pishak, V.P.; Matsyepa, I.V. (World of Medicine and Biology, 2012)
Rats poisoning with glutationperoxydasa solution leads to destruction of the cell membrane and causes activation of free radical oxidation process of macromolecules. It activates antioxidant defense system of the animal organism, which is responsible for decontamination of active form of oxygen. Effect of 0,1 % sulema (mercurius corrosivus) solution in dose of 5 mg/kg of the body weight of animals causes lowering of glutationperoxydasa activity in comparison with control not depending on the type of salt loading. 3% salt loading leads to minor indexes alteration of antioxidant enzyme activity – glutationperoxydasa in different kidneys layers in comparison with indexes of the control group. Lowering of glutationperoxydasa activity in all parts of the kidney in comparison with control under 0,75% loading with NaCl is registered.
Keywords: kidneys; glutationperoxydasa; salt loading; sulema (mercurius corrosivus); antioxidant system